2010
DOI: 10.1074/jbc.m109.053082
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal Calmodulin-binding Motif Differentially Controls Human and Rat P2X7 Receptor Current Facilitation

Abstract: P2X 7 receptors (P2X 7 R) are ATP-gated calcium-permeable cationic channels structurally unique among the P2X family by their much longer intracellular C-terminal tail. P2X 7 Rs show several unusual biophysical properties, in particular marked facilitation of currents and leftward shift in agonist affinity in response to repeated or prolonged agonist applications. We previously found the facilitation at rat P2X 7 R resulted from a Ca 2؉ -calmodulin-dependent process and a distinct calcium-independent process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 50 publications
7
60
1
2
Order By: Relevance
“…We have shown in 2005 that intracellular Ca 2+ acts as a second messenger in the large conductance channel opening in peritoneal macrophages and 2BH4 cells (Faria et al, 2005). Similar data were found by other groups (Cankurtaran-Sayar et al, 2009;Roger et al, 2008Roger et al, , 2010Schachter et al, 2008), but others did not observe this effect (da Cruz et al, 2006;Iglesias et al, 2008;Schachter et al, 2008;Virginio et al, 1999). We continued to investigate the Ca 2+ participation in more detail, and we described a major Ca 2+ dependence in the P2X7R pore formation, but we also observed Ca 2+ independent events in the same cell types (Faria et al, 2010).…”
Section: Intracellular Signalling Pathways Associated With Large Condsupporting
confidence: 79%
See 1 more Smart Citation
“…We have shown in 2005 that intracellular Ca 2+ acts as a second messenger in the large conductance channel opening in peritoneal macrophages and 2BH4 cells (Faria et al, 2005). Similar data were found by other groups (Cankurtaran-Sayar et al, 2009;Roger et al, 2008Roger et al, , 2010Schachter et al, 2008), but others did not observe this effect (da Cruz et al, 2006;Iglesias et al, 2008;Schachter et al, 2008;Virginio et al, 1999). We continued to investigate the Ca 2+ participation in more detail, and we described a major Ca 2+ dependence in the P2X7R pore formation, but we also observed Ca 2+ independent events in the same cell types (Faria et al, 2010).…”
Section: Intracellular Signalling Pathways Associated With Large Condsupporting
confidence: 79%
“…This result was also confirmed by other groups (Donnelly-Roberts et al, 2004;Faria et al, 2010;Lundy et al, 2004). However, Roger and coworkers (Roger et al, 2008(Roger et al, , 2010 reported that rat P2X7R induced large organic cation permeability ionic currents were dependent on critical residues of calmodulin binding domain when recorded in patch-clamp whole cell configuration. In this sense, the intracellular Ca 2+ concentration dependence in the P2X7R pore formation is still unclear.…”
Section: Intracellular Signalling Pathways Associated With Large Condsupporting
confidence: 78%
“…This property is a particularity of P2X 7 R and is called facilitation (Hibell et al, 2000;Roger et al, 2008Roger et al, , 2010a. This led to a seven times increase of the current density from the first to the eighth ATP application (Figure 2b).…”
Section: Human Cancer Cells Express Functional P2x 7 Rmentioning
confidence: 90%
“…Extracellular ATP acts as a signalling molecule by activating plasma membrane G protein-coupled P2Y receptors and/or ligand-gated ion channels P2X receptors (Burnstock, 2006). Among the members of the P2X receptors family, the latest cloned P2X 7 receptors (P2X 7 R) (Rassendren et al, 1997) are very unique by different features, some of them are: (1) their sensitivity to ATP (North, 2002), (2) their facilitation under successive or sustained applications of agonist (Hibell et al, 2000;Roger et al, 2008Roger et al, , 2010a and (3) the appearance of a large, non-selective membrane pore after sustained stimulations with ATP (Pelegrin and Surprenant, 2006). Recently, several tumours have been shown to express P2X 7 R at unusually high levels (Adinolfi et al, 2002;Zhang et al, 2004;Slater et al, 2004a, b;Wang et al, 2004a;Raffaghello et al, 2006;Deli et al, 2007;Solini et al, 2008), however, their functionality and involvement in the physiology of cancer cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular ATP activates plasma membrane G protein-coupled P2Y receptors and/or ligand-gated cation-permeable channels (Na + / Ca 2+ / K + ) P2X receptors (Burnstock, 2006). Among the members of the P2X receptors family, the latest cloned P2X7 receptor (P2X7R) (Rassendren et al, 1997;Surprenant et al, 1996) is very unique in its functioning by many features, such as 1) its low sensitivity to ATP (North, 2002), 2) its increasing activity, called facilitation, under successive or sustained applications of agonist (Roger et al, 2010;Roger et al, 2008), and 3) the appearance of a large, non-selective membrane pore after sustained stimulations with ATP due to the P2X7-dependent activation of pannexin-1 (Pelegrin & Surprenant, 2006). From a physiological point of view P2X7R is expressed in cells from immune lineage and its activation by extracellular ATP at concentrations upper than 100 µM is considered as an alarming signal, and is a key step in the initiation of the inflammatory cascade through the NLP3 inflammasome (Di Virgilio, 2007;Pelegrin, 2008).…”
Section: Atp-gated Ionotropic P2x7 Receptormentioning
confidence: 99%